Answer:
a = 5
Step-by-step explanation:
According to the factor theorem, if x + 2 is a factor, then by dividing the polynomial by the binomial, we are meant not to have a remainder
In this case, the remainder would be zero
So, if we set the binomial equals zero and substitute the x-value into the polynomial, we are supposed to have 0
So we have this as;
x + 2 = 0
x = -2
-2^3 -2(-2)^2 -2(a) + 6 = 0
-8-8-2a + 6 = 0
-16 + 2a + 6 = 0
2a -10 = 0
2a = 10
a = 10/2
a = 5
4 - 3 - 6x³ - 2y³ + 3x³ + 5 + 2y³
4 - 3 + 5 - 6x³ + 3x³ - 2y³ + 2y³
6 - 9x³
Answer:
first you need to divide each side by -2
Step-by-step explanation:
start with dividing by -2, then you are left with -7 = m which is the answer.
x-3y=7 2x-6y=12
You can multiply -2 in the first equation like this.
x+6y=7
2x-6y=12
Now you can eliminate 6y and -6y so cross them out and do x-2 which is -1 and 7-12 which is -5 -1/-5 would be .2
<h3 />
Answer:
$12.27
Step-by-step explanation:
.07 times 179.53 is 12.5671 so rounded to 12.27